Engineering Heterogeneous NiS2/NiS Cocatalysts with Progressive Electron Transfer from Planar p‐Si Photocathodes for Solar Hydrogen Evolution. Issue 4 (18th January 2021) - Li, Sijie; Yang, Gaoliang; Ge, Peng; Lin, Huiwen; Wang, Qi; Ren, Xiaohui; Luo, Shunqin; Philo, Davin; Chang, Kun; Ye, Jinhua
Abstract: The sluggish transfer of electrons from a planar p ‐type Si ( p ‐Si) semiconductor to a cocatalyst restricts the activity of photoelectrochemical (PEC) hydrogen evolution. To overcome such inefficiency, an elegant interphase of the semiconductor/cocatalyst is generally necessary. Hence, in this work, a NiS2 /NiS heterojunction (NNH) is prepared in situ and applied to a planar p ‐Si substrate as a cocatalyst to achieve progressive electron transfer. The NNH/Si photocathode exhibits an onset potential of +0.28 V versus reversible hydrogen electrode ( V RHE ) and a photocurrent density of 18.9 mA·cm −2 at 0 VRHE, as well as a 0.9% half‐cell solar‐to‐hydrogen efficiency, which is much superior compared with those of NiS2 /Si and NiS/Si photocathodes. The enhanced performance for NNH/Si is attributed to the contact between the sectional n ‐type semiconducting NNH and the planar p ‐Si semiconductor through a p ‐Si/ n ‐NiS/ n ‐NiS2 manner that functions as a local pn ‐junction to promote electron transfer. Thus, the photogenerated electron is transferred from p ‐Si to n ‐NiS within NNH as the progressive medium, followed by to Ni 2+ and/or S2 2− of the defect‐rich n ‐NiS2 phase as the key active sites. This systematic work may pave the way for planar Si‐based PEC applications of heterogeneous metal sulfide cocatalysts through the progressive transfer of electrons. Abstract : This study demonstrates an enhanced photoelectrochemical (PEC) hydrogen evolution system with the progressive electrons transfer form planar p ‐Si photocathodes to NiS2 /NiS heterojunction cocatalysts. The progressive transfer system is attributed to the induced local electric field assisted by the heterogenetic NiS2 /NiS including NiS as progressive media and defect‐rich NiS2 as key active sites, hence achieving an impressive PEC hydrogen evolution activity.